Pengembangan Booklet Materi Tumbuhan Paku Kelas X SMA - Dewi Septiana; Tika Mayang Sari (Universitas Pendidikan Ganesha, 2025)
This study was motivated by the limited use of learning media by teachers, which often relies solely on printed textbooks, PowerPoint presentations, or library books. Such approaches tend to make students feel bored, especially when the material is extensive, the books are thick, and the illustrations are unclear. The purpose of this research was to develop a booklet on Pteridophytes (ferns) as a learning medium for Grade X SMA/MA students. The research employed the Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation. The validation results for the material reached 78.6%, categorized as “Feasible.” Media validation also achieved a score of 78.6%, falling under the “Feasible” category. Teacher trial results obtained a score of 61, with a percentage of 93.8%, categorized as “Excellent.” Student trial results for the developed booklet gained a score of 41.3, with a percentage of 82.6%, also categorized as “Excellent.” Overall, the average percentage for the booklet was 83.4%, categorized as “Highly Feasible,” indicating that it can be effectively used in Biology learning at schools, as it meets the criteria of being practical, colorful, concise, and aligned with the learning objectives.